Young Kazakh Germans in Germany: education and multilingualism (Eurasian Journal of Philology Science and Education, 2023)
Russian Germans from Kazakhstan, or Russlanddeutsche, are ethnic Germans who lived in Russia and later in Kazakhstan before immigrating to Germany. Many representatives of the elder generation grew up speaking a German dialect known as different from Standard German, or a regional variety of Russian. Linguistic integration can still be a difficult process for Russian Germans from Kazakhstan, as language is closely tied to culture and identity. However, with time and support, many are able to successfully integrate into German society and become fluent in Standard German. This article summarizes the results of a 30-year longitudinal study of Russian-German families who immigrated with young children to Germany- The study used a mixed method of data analysis. One of the key challenges that young Russian-speaking Germans from Kazakhstan face is adjusting to the cultural norms and expectations of the German society. This can include differences in social etiquette, education, and career expectations, among other things. Despite the challenges, many young Russian Germans from Kazakhstan are able to successfully integrate into German society and build successful lives for themselves in their new home country. With the support of their families and access to resources and opportunities, these individuals are able to overcome the barriers to integration and contribute to the diversity and richness of German society.